Urban policies in the framework of the 2030 Agenda in Portugal - Medeiros, E. (XXVII Congreso Bolivia 2022 - CLAD, 2022)
Portugal, at almost 900 years old, is one of the oldest nations in the world, and with a practically unchanged national borderline with Spain. Portugal encompasses the continental mainland, located in the southwest of Europe, and two archipelagos (Madeira and Azores), located in the Atlantic Ocean. After consolidating its current borders, Portugal engaged in an epic world discovery from the mid XV century, which ended with the forging of a world empire, with colonies in several continents, which lasted until 1975, when Portugal regained a democratic system and soon applied to join what is now known as the European Union (EU) alongside Spain. Both Iberian countries joined the EU in 1986’ and soon started to incorporate policy measures which followed mainstream EU development strategies towards a more balanced, harmonious, inclusive, integrated and sustainable EU territory, Certainly, EU Cohesion Policy has had a crucial role in the overall implementation of these EU development visions, which included direct aid for urban and regional development, European several of the current United Nations (UN) 2030 Agenda development principles (UN 2015). In conclusion, despite not having a dedicated urban agenda, Portugal has used EU funded policy tools like the EU Integrated Sustainable Urban Development Strategies (SUDs) to implement some of the 11th SDG guidelines. These include integrated and sustainable urban planning and development approaches, very much aligned with the 2030 Agenda. These include the need to ensure affordable and sustainable housing, a participative, integrated and sustainable urban environment, the promotion of social diversity in cities, the safeguarding of human cultural heritage, and the reinforcement of urban resilience through risk prevention. In other words, the reading of the Portuguese SUDs as well as some thematic national development strategies confirms the effective presence of an urban 2030 Agenda in Portugal.